Evaluation of early action mechanisms in Peru regarding preparedness for El Niño - Bazo Zambrano, Juan Carlos (2019)
In this article, we provide an impact evaluation of an intervention in Peru regarding preparedness for El Niño impacts in Picsi District of Chiclayo Province in Peru’s northwestern coastal Lambayeque region. This effort involved the provision of special kits that reduce the potential damage to homes as a consequence of rainfall and floods associated with an El Nin˜o-Southern Oscillation event. Information was collected in 2016 when this Forecast-based Financing early action was activated by an El Niño forecast, and after a coastal El Niño actually struck in 2017. This dual database permits us to estimate the impact of the intervention on the damage level of homes by comparing those homes supported by the program with those homes not receiving pilot-program support. This comparison is achieved by using propensity score matching techniques, which identify the most comparable homes to the ones that were supported by the intervention. The main findings of the study suggest a positive impact of the program in terms of its effectiveness in mitigating the damage caused by the 2017 El Niño. These results suggest a drop in the scale of house damage (less damage) by around 63% for a home that received the modular kit treatment. When considering other specifications of the model, the decrease in the scale of house damage improves up to approximately 66%.